2004
DOI: 10.1021/bi049374l
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization of the Soluble Guanylate Cyclase-like Heme Domains from Vibrio cholerae and Thermoanaerobacter tengcongensis

Abstract: Soluble guanylate cyclase (sGC) is a nitric oxide- (NO-) sensing hemoprotein that has been found in eukaryotes from Drosophila to humans. Prokaryotic proteins with significant homology to the heme domain of sGC have recently been identified through genomic analysis. Characterization of two of these proteins is reported here. The first is a 181 amino acid protein cloned from Vibrio cholerae (VCA0720) that is encoded in a histidine kinase-containing operon. The ferrous unligated form of VCA0720 is 5-coordinate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
314
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 177 publications
(338 citation statements)
references
References 32 publications
24
314
0
Order By: Relevance
“…The H102G Tt H-NOX mutant was expressed and purified as previously described 4,16 and crystallized in several crystal forms. The crystal structure was solved by molecular replacement in two crystal forms (F1 and F2) and refined to 2.0 and 2.1 Å , respectively.…”
Section: Structure Determination and Analysis Of Tt H-nox H102gmentioning
confidence: 99%
See 4 more Smart Citations
“…The H102G Tt H-NOX mutant was expressed and purified as previously described 4,16 and crystallized in several crystal forms. The crystal structure was solved by molecular replacement in two crystal forms (F1 and F2) and refined to 2.0 and 2.1 Å , respectively.…”
Section: Structure Determination and Analysis Of Tt H-nox H102gmentioning
confidence: 99%
“…Expression and purification of Tt H-NOX H102G were carried out as previously described 4,16 with the addition of 10 mM imidazole to all purification buffers and expression media. It has been demonstrated that heme binding in the axial histidine H-NOX mutants can be rescued with exogenous imidazole.…”
Section: Protein Purificationmentioning
confidence: 99%
See 3 more Smart Citations